2013
DOI: 10.2337/dc12-2714
|View full text |Cite
|
Sign up to set email alerts
|

Low-Carbohydrate Diet for the Treatment of Gestational Diabetes Mellitus

Abstract: OBJECTIVEMedical nutrition therapy based on the control of the amount and distribution of carbohydrates (CHO) is the initial treatment for gestational diabetes mellitus (GDM), but there is a need for randomized controlled trials comparing different dietary strategies. The purpose of this study was to test the hypothesis that a low-CHO diet for the treatment of GDM would lead to a lower rate of insulin treatment with similar pregnancy outcomes compared with a control diet.RESEARCH DESIGN AND METHODSA total of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
2
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 17 publications
1
65
2
7
Order By: Relevance
“…Recent RCTs in women with gestational diabetes suggest that a diet higher in complex carbohydrate and fiber, low in simple sugar (low glycemic index), and lower in saturated fat may be effective in blunting postprandial hyperglycemia, preventing worsened maternal insulin resistance and excess fetal growth 2021. In a recent crossover pilot study, 16 pregnant women with gestational diabetes were randomized to a higher complex carbohydrate (60%), lower fat (25%) diet or a conventional low carbohydrate (40% of calories), higher fat (45% of calories) diet at the time of diagnosis 22.…”
Section: Lifestyle Modificationsmentioning
confidence: 99%
“…Recent RCTs in women with gestational diabetes suggest that a diet higher in complex carbohydrate and fiber, low in simple sugar (low glycemic index), and lower in saturated fat may be effective in blunting postprandial hyperglycemia, preventing worsened maternal insulin resistance and excess fetal growth 2021. In a recent crossover pilot study, 16 pregnant women with gestational diabetes were randomized to a higher complex carbohydrate (60%), lower fat (25%) diet or a conventional low carbohydrate (40% of calories), higher fat (45% of calories) diet at the time of diagnosis 22.…”
Section: Lifestyle Modificationsmentioning
confidence: 99%
“…'Other' diet and exercise trials Nine trials 204,206,208,209,212,[215][216][217]219 were too methodologically diverse to allow pooling of data. Six trials 206,209,212,215,217,219 compared two different types of diets, one trial 204 compared exercise to insulin use, one trial compared diet and insulin to diet alone, and one compared exercise with diet 216 ( Table 28).…”
Section: Treatments For Gestational Diabetes: a Systematic Reviewmentioning
confidence: 99%
“…Asemi 215 Asemi 215 Asemi 215 Cao 217 Cao 217 Cypryk 209 Cypryk 209 Cypryk 209 Louie 219 Louie 219 Moreno-Castilla 206 Rae 212 Metformin, in addition to performing well, may also be preferred by women, as it is administered orally and can be stored at room temperature as opposed to insulin, which requires subcutaneous injection and refrigerated storage. Metformin is associated with gastrointestinal upset, however, which may affect compliance; unfortunately, few trials report side effects or participant satisfaction, quality of life or wellbeing, which should be examined by future trials.…”
Section: Pharmacological Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…One RCT in 107 GDM patients showed that a low-GI diet (compared with the intake of all types of carbohydrates with varying GI) was not more efficient in the improvement of glycaemic control (14) . Inconsistent results were observed in other studies (15) , possibly due to insufficient appreciation of the total amount of carbohydrate in the foods, which is the major determinant for blood glucose response.…”
mentioning
confidence: 58%